The main setbacks promoted by the Brazilian Forestry Act of 2012: main actors, interests, and the principle of the prohibition of environmental backsliding - Ferreira Carvalho, Edson; Giessen, Lukas; Fernández, Encarnación (Revista de Derecho Ambiental, 2019)
The objective of this study is to analyze the main setbacks introduced by the 2012 Brazilian Forestry Act and the political context of its formulation. The analysis is based on a comparison of the rules that regulate the Institutes of the Permanent Preservation Area (APP) and Legal Reserve Area (ARL) in private agrarian properties by the Forest Laws of 1965 and 2012. As well as the positions and interests of the most relevant ac-tors in relation to the protection of natural forests, highlighting the great influence of the agricultural sector. The study demonstrates that the 2012 Forestry Law was formulated to weaken the two main legal institutes for protecting native vegetation in private agrarian properties, legalizes illegal occupations of the two protected areas, amnesties the offenders and increases the territory susceptible of deforestation. In spite of the legislative alterations promoted by the Forest Act of 2012 characterize an indisputable violation to the constitutional guarantee of prohibition of environmental backsliding and of the duties of environmental protection of the Brazilian State, the Federal Supreme Court endorsed them, based on the principle of the division of powers.